Analisis Faktor Keterlambatan Dominan Pada Proyek Pemeliharaan Jalan (Studi Kasus: Jalan Seksi Sp. Dodinga – Sofifi – Akelamo – Payahe – Weda) - Abdul Hamid Payapo; Nurmaiyasa Marsaoly; Abdul Gaus; Ichsan Rauf; Raudha Hakim (Fakultas Teknik, 2023)
Road maintenance work or road preservation is very important to be carried out as a government effort to maintain the functional sustainability of the road. The delay in the implementation of this activity will not only have an impact on accessibility between regions, but will also cause losses for the contractor and project owner. The factors causing delays in the implementation of road preservation work vary widely and are different in each region. Thus, an understanding of these factors will provide important information in the management of future projects. This study conducted to analyze the dominant factors that cause the delays of road preservation projects in North Maluku, where the case study is in the Sp. Dodinga – Sofifi – Akelamo – Payahe – Weda, this road has length of ± 141 km. Respondents in the study are people who are directly involved in the implementation of this work. A statistical approach was carried out in this study, where the independent variables used included: Finance (X1), Human Resources (X2), Materials (X3), Equipment (X4), Work Implementation Methods (X5), Design Changes (X6), and Work Environment (X7), while for the dependent variable is Time (Y1). The results of this study indicate that the dominant factors influencing the timely completion of road preservation work at the study location are Finance (X1), Human Resources (X2), Materials (X3), and Equipment (X4) with a percentage value of 43.89%.